San Fernando: utopia or unfinished project? - Murillo, Juan Pablo (2013)
The study analyzes the various modernization projects at the Faculty of Medicine San Fernando, in the context of a serious institutional crisis at the end of the XXth century. Beginning from the thinking collective and thinking style categories proposed by Ludwick Fleck, we study the social and historical processes related to the different initiatives displayed in the ancient Peruvian school of medicine. Analysis of the different initiatives identified lead us to the hypothesis that San Fernando’s crisis as an academic collective is based in the proper contradictions of an unfinished institutional project that also manifests cyclically asynchronous and dysfunctional to the complex and changing Peruvian society’s institutional and cultural environment. The study systematizes the main characteristics of the different institutional modernization projects. Following an analysis of the current Peruvian health sector context and starting from the processes identified, we propose a development agenda oriented to generate an academic accumulation and growth cycle that constitutes a transition stage in front of the challenges posed by the XXIth century to the San Fernando collective members.